(untitled) (Research, Society and Development, 2021)
Autism Spectrum Disorder (ASD) is a group of early onset neurodevelopmental disorders characterized by impaired social and communication skills and behavior, and may affect a person’s ability to communicate, establish relationships, and respond appropriately to the surrounding environment. There are still few instrumental resources for the diagnosis of people with suspected autism, and there is no biological marker that enables a precise test to confirm or not this diagnosis. However, after the diagnosis by a qualified health professional, in more severe cases, a drug intervention is required, aiming to control the condition, with the use of pharmacological classes: Atypical Antipsychotics (AAPs), the Selective Serotonin Reuptake Inhibitors (SSRIs), Antidepressants, Mood Stabilizers and Anticonvulsants. In this context, the present work aims to make a comparison of serotonin receptor drugs in children with Autistic Spectrum Disorder, from a bibliographic and exploratory study. From the results obtained, it was found that the most commonly used drugs in Brazil for children with Autistic Spectrum Disorder are: Fluoxetine, Citalopram, Paroxetine, Sertraline, Fluvoxamine and Escitalopram. Each drug has its own indication, but with different results and similar actions, since the differences in the structure of the compound intervene in the pharmacokinetic profiles.